Metagenomic Investigation Uncovers Presence of Probiotic-Type Microbiome in Kalparasa® (Fresh Unfermented Coconut Inflorescence Sap) - Gopal, Murali; Shil, Sandip; Gupta, Alka; Hebbar, K. B.; Arivalagan, M. (Frontiers in Microbiology, 2021)
The phloem sap tapped from unopened inflorescence (spadix) of coconut palm using a novel collecting device, “coco-sap chiller,” has been branded Kalparasa® (henceforth as Kalparasa in the text) to distinguish its properties not found in sap harvested by traditional methods. To know its hitherto unidentified microbiome profile, we employed high-throughput sequencing to uncover the bacteriome and mycobiome in fresh and 12-h fermented samples. Fresh Kalparasa had a pH of 7.2, which dropped to 4.5 after 12 h, signifying fermentation of the sap. Diversity analysis indicated fresh Kalparasa having higher bacterial species than the fermented one. Contrary to this, fresh sap had lower fungal/yeast diversity than the fermented sample. Fresh Kalparasa had relatively higher abundance of probiotic-type Leuconostoc genus followed by equal proportions of Gluconobacter, Acetobacter, and Fructobacillus. The 12-h fermented Kalparasa showed a significant increase in Gluconobacter with a sharp decrease in Leuconostoc. Mycobiome data revealed fresh Kalparasa to be preponderant in Saccharomyces and Hanseniaspora genera of yeasts while the fermented sap had higher representation of Hanseniaspora and Cortinarius and lesser Saccharomyces. This suggested that the fermentation of Kalparasa was probably driven by symbiotic culture of bacteria and yeasts (SCOBY), particularly acetic acid bacteria and non-Saccharomyces yeasts. The bacteriome-function predictions highlighted the enrichment of glycerophospholipid, ABC transporters, purine, and pyrimidine metabolisms. Based on our findings, Kalparasa containing large population of Leuconostoc mesenteroides, Fructobacillus fructosus, Saccharomyces cerevisiae, and Hanseniaspora guilliermondii can be promoted as a healthy “unfermented” plant edible food containing live probiotic-type microbiome during its consumption.